Implementasi Sistem Penjaminan Mutu Internal (SPMI) BERBASIS Siklus PPEPP Dalam Penguatan Budaya Mutu Sekolah: Studi Kasus Di SMPN 1 Kota Prabumulih - Erly Zahara; Tati Lasmita; Saipul Annur; Asri Karolina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the implementation of the Internal Quality Assurance System (IQAS) based on the PPEPP cycle in strengthening the quality culture at SMPN 1 Prabumulih City. The study employed a qualitative approach with a case study design through interviews, observations, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while data validity was ensured through triangulation and member checking. The findings indicate that the implementation of the PPEPP-based IQAS has been carried out systematically through the stages of standard setting, standard fulfillment, evaluation, continuous improvement, and the establishment of new standards. This implementation has effectively strengthened the school's quality culture, as reflected in increased quality awareness, active participation of school members, and continuous improvement in educational servicess. Supporting factors include the principal’s leadership and technical assistance from school supervisors and the Institute for Educational Quality Assurance (LPMP). Meanwhile, the main challenges are limited financial resources and the high workload of teachers.